2008
DOI: 10.1212/01.wnl.0000296829.66406.14
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor reorganization by proprioceptive training in musician's dystonia and writer's cramp

Abstract: The intervention effect depends on the pre-interventional sensorimotor organization (SMO). In focal hand dystonia, particularly in musician's dystonia, it is possible to retrain an abnormal SMO toward a more differential pattern, which has potential implications for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 37 publications
(65 reference statements)
5
48
0
Order By: Relevance
“…Recent studies comparing MD and WC patients using transcranial magnetic stimulation suggested pathophysiologic differences between the two conditions. 16,17 Given a possible common genetic cause of MD and WC in at least a subset of patients as confirmed by the present study, however, these neurophysiologic differences could be interpreted as a secondary rather than a primary phenomenon.…”
Section: Patients and Familiessupporting
confidence: 59%
“…Recent studies comparing MD and WC patients using transcranial magnetic stimulation suggested pathophysiologic differences between the two conditions. 16,17 Given a possible common genetic cause of MD and WC in at least a subset of patients as confirmed by the present study, however, these neurophysiologic differences could be interpreted as a secondary rather than a primary phenomenon.…”
Section: Patients and Familiessupporting
confidence: 59%
“…However, we wish to highlight the involvement of trigger factors linked to the specific requirements of playing music and fine motor control (playing speed, trills, vibrato, etc.). This is consistent with sensorimotor integration and inhibitory control alterations described in this disorder, 29,30 and it may be especially relevant for selecting repertoire to be played during the musician's rehabilitation. When patients are students, this may require cooperation from their teachers.…”
Section: Discussionsupporting
confidence: 85%
“…The alpha-band power and coherence S1-M1 coherence increases could be the effect of both abnormal primary sensorimotor representations as well as a strategy to compensate for the loss of physiological inhibition. A better understanding of those mechanisms could give the chance for the development of neurophysiology-driven therapeutic approaches (Zeuner et al, 2002;Rosenkranz et al, 2008;Tinazzi et al, 2009b). In fact, pathogenesis-targeted treatment is still elusive in dystonias and rehabilitative techniques based on sensory-motor recalibration (sensorimotor retuning, sensory/proprioceptive retraining, limb immobilization, selective peripheral denervation, well-fitted braces and proprioceptive training) have failed to demonstrate sustained, long-term benefits (for a review, see Jankovic, 2006).…”
Section: Discussionmentioning
confidence: 99%